Follow‐up of human adenovirus viral load in pediatric hematopoietic stem cell transplant recipients. Issue 3 (16th January 2021) - Peker, Bilal Olcay; Tüysüz Kintrup, Gülen; Sağlık, İmran and Can Sarınoğlu, Rabia and Güler, Elif and Mutlu, Derya and Küpesiz, Osman Alphan and Çolak, Dilek
Abstract: Background: The spectrum of human adenovirus (HAdV)–related disease is broad, and the virus acts on many organs and systems in hematopoietic stem cell transplantation (HSCT) recipients. We aimed to evaluate the effect of HAdV‐DNA positivity with clinical and laboratory findings 4 months after HSCT. Methods and results: We retrospectively investigated HAdV‐DNA in 153 HSCT recipients (≤18 years) by quantitative real‐time polymerase chain reaction (RealStar; Altona Diagnostics). The results of samples from January 2014 to December 2017 are included. HAdV‐DNA was positive for at least one sample type in 50 (32.67%) patients. HAdV‐DNA positivity rate was 8.92% ( N : 145/1625), 40.25% ( N : 64/159), and 25% ( N : 2/8) for plasma, stool, and urine samples, respectively. HAdV‐DNA was positive in the plasma of 38 (24.83%) patients at a median 16 (range: 1–58 days) days after HSCT. The mortality rate was 23.68% and 6.95% in plasma HAdV‐positive and HAdV‐negative patients ( p = .014). Moreover, HAdV‐DNA positivity had an impact on overall survival for allogeneic‐HSCT ( p = .013), with the cumulative effect including graft‐versus‐host disease state in multivariate analysis ( p = .014). Conclusions: Plasma HAdV‐DNA positivity is a potential influencer that decreases survival in the early post‐transplant period. Due to the high mortality rates, close monitoring is required of HAdV infections after HSCT with sensitive methods, especially at the early stage.